Non-destructive testing of jute–polypropylene composite using frequency-modulated thermal wave imaging. (April 2015) - Banerjee, D; Chattopadhyay, SK; Chatterjee, K; Tuli, S; Jain, N; Goyal, I; Mukhopadhyay, S
A recently developed frequency-modulated thermal wave imaging (FMTWI) has been applied for subsurface defect detection of jute fibre-reinforced polypropylene (PP) matrix composite. Composites are subject to manufacturing and in-service defects like voids, delamination, cracks and so on. Active thermography like lock-in thermography (LT) and pulsed thermography (PT) has been widely used for non-destructive testing of composites and laminates. FMTWI may be viewed as a superposed LT, wherein multiple frequency response is obtained through single measurement. It is very much suitable for newly developed material for which the thermal properties are not well established, thereby impeding the choice of appropriate frequency for conventional LT. In this article, FMTWI is applied to detect and characterize artificially generated subsurface defects in jute–PP composite. The measurements also show the effect of frequency on the depth of defect detection and accuracy.